Psychological Aspects of Employment of Modern Graduates of High Schools (Round table «Partnership in the Field of Training» Yelets, June 26, 2018) - Budyakova T.P.; Polyakova T.А. (Психолого-педагогические исследования, 2018)
This material is a short report on the round table "Partnership in the field of training of personnel" held on June 26, 2018 in Yelets, organized in the framework of the All-Russian scientific and practical conference with international participation "Adaptation to the labor market of young specialists and facilitating their employment ". The round table was attended by more than 50 people, including representatives of Lebanon, Bulgaria, Germany and other countries. The main directions of discussion of the stated problem are presented and the most important elements that provoked discussions during the exchange of views at the round table. The emphasis is on the psychological and pedagogical aspects of the issues under consideration. Issues of the round table were interdisciplinary, but the main line of discussion was the psychological problems of the modern labor market, employment, employment and partnership in this area. In particular, the subject of discussion were the issues of forming the personality qualities of the graduate, contributing to his successful employment, the psycho-logical aspects of labor adaptation of graduates of higher education institutions, the psychology of self-reflection in employment, etc. Presentations were made by academics, conducting psychological, pedagogical and social studies -psychological research in the field of human resources and employment, as well as employers (employers' representatives), managers and employees of public services for yatosti population. During the discussions, existing gaps and shortcomings were identified in solving the problems of finding employment for graduates, and suggestions were made to improve mechanisms for solving employment problems in Russia using the potential of psychological science.